ACTN3 association on maximal muscle power, after 6 weeks of power training - Vuksanovikj, Vladimir; Aceski, Aleksandar; Hristovski, Robert; Popovski, Zoran (Faculty of physical education sport and health, 2021)
The research tried to discover/find out [1] whether the success of transformation of max muscle power will be just because of the training sessions? Or perhaps [2] the genetic potential of examinees will be important to make bigger and faster transformation of max muscular power. The experimental program was applied within (N) 21 examinees, age of 18-20 years, non-athlete population, for a period of 6 weeks. The programme included exercises for transformation of the maximal strength component of the flexors and extensors muscles on the elbow of the examinees' non-dominant arm (load- 90-95% of one repetition maximum). Three tests for one repetition maximum (flexion+ extension) were performed (program start, 3th and 6th week). Mutation of ACTN3 genotype allele, of the examinees, were analysed, according to establish three types of examinees: (type I) slow-oxidative - XX type/group, (type IIA) fast oxidative/glycolytic RX type/group and (type IIB) fast glycolytic -RR type/group. The three groups of examinees (XX, RR, XR) do not differ in terms of the achievements of one repetition maximum (flexors/extensors) after 3th and after 6th week. The genetic predisposition of the muscle tissue for strength capacities is not always decisive for the transformation of the maximal strength abilities.
Keywords: 1RM; ACTN3; flexion; extension; training